Pengembangan Media Monopoli Bahasa Berbantuan Flash Card Digital - Revana Azizah; Satriyani, Febrianti Yuli (Jurnal Pendidikan Dasar, 2025)
This study aims to develop, assess the feasibility, and test the effectiveness of the Monosa (Language Monopoly) learning media supported by Digital Flash Cards to improve emergent reading skills of first-grade students at SDN Kayu Putih 03. The research employed a Research and Development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Validation results indicate that the Monosa media was rated "very good" by media, content, and language experts. Furthermore, trials with students showed a significant improvement in emergent reading skills, as evidenced by the increase in average scores between the pretest and posttest. Therefore, the Monosa media supported by Digital Flash Cards is proven to be effective as a learning aid for teaching emergent reading to first-grade elementary students.